Timing of hydrocortisone therapy in neonates with shock: a systematic review, meta-analysis, and clinical practice guideline - Ramaswamy, Viraraghavan Vadakkencherry; Kumar, Gunjana; Pullattayil S, Abdul Kareem; Aradhya, Abhishek S.; Suryawanshi, Pradeep; Sahni, Mohit; Khurana, Supreet; Saini, Shiv Sajan; K, Ravishankar; Dhir, Shashi Kant; Chawla, Deepak; Kumar, Praveen; et al. (Frontiers in Pediatrics, 2025)
BackgroundThe effect of the timing of initiation of hydrocortisone in neonatal shock has not been evaluated. The objective of this systematic review was to compare the effect of earlier vs. later initiation of hydrocortisone in neonatal shock.MethodsMedline, Embase, and CENTRAL were searched from inception until 15 May 2024. Randomized controlled trials (RCTs) and non-RCTs were eligible for inclusion. A random effects meta-analysis was used to synthesize the data. The evidence certainty was evaluated according to Grading of Recommendations Assessment, Development, and Evaluation (GRADE). A clinical practice guideline was formulated as recommended by the GRADE group.ResultsOf the 3,757 titles and abstracts screened, 20 studies were included: 7 RCTs and 13 non-RCTs. While clinical benefit or harm could not be ruled out for the outcome of mortality from the meta-analysis of the RCTs [early initiation risk ratio (RR): 0.46, 95% confidence interval (CI): 0.03–7.92; late initiation RR: 0.43, 95% CI: 0.12–1.47], the non-RCTs included in the narrative review suggested that late hydrocortisone initiation might be associated with increased risk of mortality. The meta-analysis indicated that early and late hydrocortisone administration may be associated with an increased response to treatment therapy (early initiation RR: 1.85, 95% CI: 1.26–2.71; late initiation RR: 2.50, 95% CI: 1.16–5.39). Late hydrocortisone initiation may increase the risk of necrotizing enterocolitis (NEC) ≥ stage 2 (RR: 2.46, 95% CI: 1.19–5.08). The evidence certainty was very low for most of the outcomes evaluated.ConclusionThe early use of hydrocortisone in neonates with shock requiring vasopressors is associated with better outcomes and no major adverse effects. Later institution of hydrocortisone therapy in neonatal shock may improve the response to therapy but may be associated with adverse outcomes including mortality and NEC. The results are to be interpreted with caution as the evidence certainty was predominantly very low.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023432169, identifier: CRD42023432169.